Pengaruh Pembelajaran Berbantuan Geogebra Berbasis Batik Nusantara Terhadap Computational Thinking Skill Siswa - Herzani, Amrina Qurotul Aina Nur; Milawati, Eni; Nariswari, Diva Auberta; Pratama, Dafian Ilham; Saputri, Ravelia Maylinda; Apriandi, Davi (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2024)
This research aims to determine the effect of geogebra-assisted learning based on Indonesian batik on students' computational thinking. This research uses the Quasi Experiment Design method with the non-equivalent group design. Hypothesis testing uses the non-parametric Mann-Whitney U Test because the data is not normally distributed. The test was carried out using the IBM SPSS Statistics 25 program. This research was carried out at SMPN 8 Madiun on 4 - 18 September 2023 with geometric transformation material. The population in this study were all class IX students at SMPN 8 Madiun, totaling 219 students. The samples were taken randomly, with 26 class IX A students as the control class and 23 class IX E students as the experimental class. The instrument of this research is a computational thinking test. This test is needed to measure students' CT in learning geometric transformation material after the treatment is given. Before the instrument is administered, validity and reliability are proven. The research results show that based on the